Distance Education and its Different Forms of Learning – New Learners? - dos Santos Caparróz Carvalho, Adriana; Lima Paniago Lopes, Maria Cristina; Martins Régis dos Santos, Rosimeire (Revista Brasileira de Aprendizagem Aberta e a Distância, 2008)
This article is part of a research carried out by a Group of Studies and Researches about Educational Technology and Distance Education (GETED) and it aims to enrich the theory about how to learn at the virtual context reflecting at the students learning conceptions from this modality. With the objective of analysing the relation between the Distance Education and the new forms of learning, if we can consider them as new, we start the work articulating the concepts of information and knowledge and the new ways of knowledge with the participants excerpts of a graduation course offered at the distance modality. After that, we discuss the question of autonomy at the distance learning process, also with some exemplifications of the collected data at the offered course. The next theme in discussion is the collaborative learning with focus on the interaction. We end the article pointing at some conclusions about how the students see the new learning at the distance education context.